Investigation of phases and textures of binary V-Si coating deposited on vanadium-based alloy (V-4Cr-4Ti) using electron backscatter diffraction. Issue 1 (April 2015) - Nowakowski, P; Ubhi, H S; Mathieu, S
Abstract: Barrier coating consisting of binary silicide compounds Six Vy were deposited on a V-4Cr-4Ti vanadium alloy substrate. Samples were cycled in a furnace for 122h at 650°C and 1100°C. The electron backscattered (EBSD) combine with X-ray energy dispersive spectrometry (EDS) techniques were employed to identify the phases in the multi-layered coating and to determine growth texture for each phase. The microstructure evolutions occurringduring cycling at 1100°C in the protective coating and the crystal orientation relationships between Six Vy were determined.